Generation Mean Analysis Reveals the Predominant Gene Effects for Grain Iron and Zinc Contents in Pearl Millet - Pujar, Mahesh; Govindaraj, Mahalingam; Gangaprasad, S.; Kanatti, Anand; Gowda, T. H.; Dushyantha Kumar, B. M.; Satish, K. M. (Frontiers in Plant Science, 2022)
Pearl millet [Pennisetum glaucum (L.) R. Br.] is a climate-resilient dryland cereal that has been identified as a potential staple food crop that can contribute to alleviating micronutrient malnutrition, particularly with respect to grain iron (Fe) and zinc (Zn) content, in Sub-Saharan Africa and India. In this regard, an understanding of the inheritance pattern of genes involved in Fe and Zn content is vital for devising appropriate breeding methods to genetically enhance their levels in grains. In this study, we aimed to determine the genetic effects underlying such inheritance and their interactions based on generation mean analyses. Four experimental crosses and their six generations (P1, P2, F1, BCP1, BCP2, and F2) were independently evaluated in a compact family block design in the 2017 rainy and 2018 summer seasons. Analysis of variance revealed highly significant mean squares (P < 0.01) among different generations for grain Fe and Zn contents. Six-parameter generation mean analyses revealed a predominance of additive genetic effect and a significant (P < 0.05) additive × dominant interaction for grain Fe content. The additive genetic effect for grain Zn content was also highly significant (P < 0.01). However, interaction effects contributed minimally with respect to most of the crosses for grain Zn content and hence we assume that a simple digenic inheritance pattern holds true for it. Furthermore, we established that narrow-sense heritability was high for grain Fe content (> 61.78%), whereas it was low to moderate for grain Zn content (30.60%–59.04%). The lack of superior parent heterosis coupled with non-significant inbreeding depression for Fe and Zn content in grains further confirmed the predominance of an additive genetic effect. These findings will contribute to strategizing a comprehensive breeding method to exploit the available variability of grain Fe and Zn contents for the development of biofortified hybrids of pearl millet.